Implications of The Influence of Parental Attention and Learning Facilities on Online Learning in Primary Schools - Yusni Arni; Huliman Abdul Gofur; Muljadi Muljadi; Ahmad Lazuardi Al-Fitrie (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
The recent surge in forest and land fires across Kalimantan has had far-reaching impacts, notably on the educational landscape, including the process of teaching and learning in schools. This quantitative study aims to explore the direct and indirect influences of parental attention and learning facilities on the academic achievements of elementary school students. The investigation incorporates the mediating role of motivation and utilizes a survey methodology with questionnaires as the primary data collection tool. The research, conducted in the Timpah sub-district of Kapuas Regency, Central Kalimantan, involves a sample of 200 elementary school students. Employing the Smart PLS 4 structural equation model, the study examines seven hypotheses, revealing the significant effects of parental attention and learning facilities on the efficacy of online learning processes. The findings aspire to impart valuable insights to educators and parents, underscoring the pivotal roles of parental engagement and the provision of adequate facilities in ensuring successful learning outcomes.